A comparative study on the liabilities of medical practitioner in blood transfusion in Malaysia and United Kingdom / Noor Syuhada Hassim …[et al.] - Hassim, Noor Syuhada; Zainuddin, Norhafizah; Razali, Siti Hamizah; Mat Tasim, Sufinah; Sanusi, Zuriyanti (2010)
The issue of medical negligence in blood transfusion usually gives rise to the question of who should be responsible to the act of misconduct. The patients had suffered the loss due to the treatment that they consented. Once this happen, the debate issue on the right of the patient will be heated argument between the victims and the medical practitioner. The liabilities should lie on the person who has done the misconduct. There are numbers of cases where the patient has received contaminated blood during the blood transfusion. The patients do faced a lot of problem in order to make claim on the negligence of medical practitioner. Making claims on the negligence act of a medical practitioner do increase the burden they have already bear. This research paper is on the area of medical law. Generally it deals with medical negligence, particularly on blood transfusion. Discussion will be on the liabilities of medical practitioner in blood transfusion in Malaysia and United Kingdom. It attempts to discover whether the law in Malaysia is adequate in governing the conduct of medical practitioner. The comparison between the law of Malaysia and United Kingdom regarding the liabilities of medical practitioner in blood transfusion will be analysed with the intention of making possible recommendation to fix the inadequacy of the Malaysian Law.